The Effect of Employee Empowerment on Performance through Job Satisfaction (Study of Employees of the Customs Supervision and Service Office of Intermediate Type C Kendari) - Nur, Muh.; A. Sabilalo, Mahmudin; Hertasning, Hertasning (Jurnal Multidisiplin Indonesia, 2025)
This study aims to analyze the impact of empowerment on employee performance, job satisfaction on employee performance, and empowerment on performance through job satisfaction. The study uses the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with a sample size of 57 employees from the Customs and Excise Supervision and Service Office Type Madya Pabean C Kendari. The results show that empowerment has a positive effect on employee performance, although its impact is smaller compared to the relationship between job satisfaction and performance. Empowerment provides employees with the opportunity to work more independently and responsibly, which in turn can improve their performance. Additionally, empowerment has a positive and significant effect on job satisfaction, indicating that job autonomy, recognition of contributions, and opportunities for growth can enhance job satisfaction. Furthermore, job satisfaction has a positive and significant impact on employee performance, with higher job satisfaction levels leading to better performance. Empowerment also positively influences employee performance through increased job satisfaction, meaning that successful empowerment that improves job satisfaction will contribute to enhanced employee performance